Formulation Development and Evaluation of Leaf Extract of Ficus benghalensis for Antidiabetic Activity - Laware, Ravindra B.; Pulate, Shubhangi P.; Dighe, Santosh B; Bhawar, Sanjay B (Journal of Drug Delivery and Therapeutics, 2019)
Herbal products are known for their inherent property i.e. comparatively safe and economic. In present study, leaf extract of ficus benghalensis was evaluated for antidiabetic activity. The aim of the research work was to formulate and evaluate capsule dosage form of ethanolic extract. Leaves of Ficus benghalensis collected from local area of Ahmednagar district and shade dried. Ethanolic, Hydroalcoholic and petroleum ether extracts were prepared using soxhlet apparatus. Extracts were screened for antidiabetic activity using alloxan induced diabetes in rats. Oral glucose tolerance test was measured as parameter to check antidiabetic activity. Ethanolic extract was found most effective among them. Granules were prepared using ethanolic ectract and filled in capsule.  Capsule were evaluated for parameters including uniformity of weight, disintegration time.Keywords: Ficus benghalensis, Ethanolic extract, Antidiabetic activity